2019
DOI: 10.1093/nar/gkz598
|View full text |Cite
|
Sign up to set email alerts
|

Functional interplay between Mediator and RNA polymerase II in Rad2/XPG loading to the chromatin

Abstract: Transcription and maintenance of genome integrity are fundamental cellular functions. Deregulation of transcription and defects in DNA repair lead to serious pathologies. The Mediator complex links RNA polymerase (Pol) II transcription and nucleotide excision repair via Rad2/XPG endonuclease. However, the functional interplay between Rad2/XPG, Mediator and Pol II remains to be determined. In this study, we investigated their functional dynamics using genomic and genetic approaches. In a mutant affected in Pol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 64 publications
3
41
0
Order By: Relevance
“…Increasing the number of CpG dinucleotides in viral genomes is a promising vaccine approach; attenuated infection phenotypes caused by recoded vaccine candidates, however, may depend on the expression of cellular components targeting viral CpG dinucleotides (7,15). Thus, population-based studies on infection caused by CpG-recoded viruses will foster further application of the approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the number of CpG dinucleotides in viral genomes is a promising vaccine approach; attenuated infection phenotypes caused by recoded vaccine candidates, however, may depend on the expression of cellular components targeting viral CpG dinucleotides (7,15). Thus, population-based studies on infection caused by CpG-recoded viruses will foster further application of the approach.…”
Section: Discussionmentioning
confidence: 99%
“…Third, restriction of infection is not mediated through translation impairment, disruption of an RNA structure, or stress, interferon, and apoptosis pathways activated through conventional pattern recognition receptors (4,(10)(11)(12). Finally, zinc-finger antiviral protein (ZAP) targets recoded human immunodeficiency virus 1 (HIV-1) and echovirus 7 by directly binding to CpG-enriched genomic regions (9,14); subsequently, synergy or complementation of ZAP function by oligoadenylate synthetase 3, RNase L (15) and cytoplasmic protein KHNYN (16) is capable of inhibiting replication of viruses containing the elevated number of CpG dinucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the results of our analysis were verified by an in vivo experiment. The maintenance of transcriptional fidelity and genome integrity is essential for cellular functions, while deregulation of transcription and defects in DNA repair can cause serious pathologies, including HN (Trudu et al, 2013;Georges et al, 2019). It was reported that the absence of POLR2I significantly reduces transcriptional accuracy (Nesser et al, 2006) and also leads to defects in replication fork progression (Felipe-Abrio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, it has been demonstrated that cellular Zinc-finger antiviral protein (ZAP) targets recoded viruses by specifically binding to genomic regions enriched in CpG dinucleotides [3,4]. Subsequently, synergy or complementation of ZAP function by oligoadenylate synthetase 3, RNase L, and cytoplasmic protein KHNYN inhibits replication of viruses containing an elevated number of CpG dinucleotides [5,6].…”
Section: Introductionmentioning
confidence: 99%